Hypoxic events stimulate nitrogen recycling in a shallow salt‐wedge estuary: The Yarra River estuary, Australia - Keryn L. Roberts; Vera M. Eate; Bradley D. Eyre; Daryl P. Holland; Perran L. M. Cook (Limnology and Oceanography, 2012)
The Yarra River estuary is a salt‐wedge estuary prone to periods of stratification‐induced anoxia and hypoxia (O 2 −1 ) during low‐flow events. Nitrate reduction pathways were examined using the 15 N isotope pairing technique in intact sediment cores, emulating in situ conditions, to evaluate the fate of NO during changing oxygen conditions. Water‐column concentrations of dissolved inorganic carbon (DIC), O 2 , NH, and NO x (NO + NO) were also measured to examine any deviation from conservative behavior (denoted Δ) in response to oxygen variability within the estuary. The estuary was a source of NH in the anoxic bottom waters. Whole‐system estimates using deviations from conservative behavior and core incubations were in good agreement and showed that NH was regenerated more efficiently relative to DIC under hypoxic conditions. For the whole system, mean ΔDIC : ΔNH ratios under oxic (85 ± 33) and hypoxic (20 ± 3) conditions were significantly different. The more‐efficient NH regeneration during hypoxia was attributed to rapid mineralization rates and cessation of nitrification; dissimilatory nitrate reduction to ammonium (DNRA) was not a significant contributor. Unexpectedly, the denitrification : DNRA ratio was significantly higher under hypoxic conditions, with denitrification contributing 99.1% ± 0.3% of total nitrate reduction. DNRA rates were significantly higher during oxic conditions (123.5 ± 30.7 µmol m −2 h −1 ) when compared with rates during hypoxia (0.6 ± 0.1 µmol m −2 h −1 ). The increase in DNRA in the presence of oxygen was attributed to the alleviation of NO limitation during these conditions.

The “salt wedge pump”: Convection‐driven pore‐water exchange as a source of dissolved organic and inorganic carbon and nitrogen to an estuary - Isaac R. Santos; Perran L. M. Cook; Louissa Rogers; Jason de Weys; Bradley D. Eyre (Limnology and Oceanography, 2012)
Hypoxia and anoxia in coastal waters have typically been explained by the respiration of sinking organic matter associated with nutrient over‐enrichment and phytoplankton blooms. Here, we assess whether submarine groundwater discharge and seawater recirculation in sediments can explain widespread chemical anomalies, including low dissolved oxygen, in salt wedge estuaries. We rely on high‐resolution radon (a natural groundwater and pore‐water tracer), and dissolved carbon concentrations and stable isotope observations in the Yarra River estuary in Melbourne, Australia. Radon was highly enriched within the salt wedge, demonstrating enhanced pore‐water exchange at this area. We use the term “salt wedge pump” to describe convection‐driven advective pore‐water exchange at the sediment–water interface during the upstream propagation of the salt wedge. Radon‐derived convection‐driven pore‐water exchange rates within the salt wedge were estimated at 2.8 cm d −1 , a value equivalent to 2.4% of the total river freshwater runoff to the estuary. Pore‐water exchange led to pulsed dissolved inorganic carbon (DIC) and ammonium fluxes ∼ 10‐fold higher than measured diffusive fluxes. In contrast, diffusive sediment oxygen uptake was 5‐fold higher than oxygen uptake related to advective pore‐water exchange. Estimated fluxes, associated with the nonconservative DIC, δ 13 C‐DIC, and ammonium behavior within the estuary support convective pore‐water exchange as a major source of DIC and ammonium to the estuary, but not of dissolved organic carbon, nitrate, dissolved organic nitrogen, and anoxia. Accounting for seawater recirculation in sediments may help reconcile unbalanced carbon and nitrogen budgets in several coastal systems.

Quantifying denitrification in rippled permeable sands through combined flume experiments and modeling - Adam J. Kessler; Ronnie N. Glud; M. Bayani Cardenas; Morten Larsen; Michael F. Bourke; Perran L. M. Cook (Limnology and Oceanography, 2012)
We measured denitrification in permeable sediments in a sealed flume tank with environmentally representative fluid flow and solute transport behavior using novel measurements. Numerical flow and reactive transport models representing the flume experiments were implemented to provide mechanistic insight into the coupled hydrodynamic and biogeochemical processes. There was broad agreement between the model results and experimental data. The model showed that the coupling between nitrification and denitrification was relatively weak in comparison to that in cohesive sediments. This was due to the direct advective transport between anoxic pore water and the overlying water column, and little interaction between the mostly oxic advective region and the underlying anoxic region. Denitrification was therefore mainly fueled by nitrate supplied from the water column. This suggests that the capacity of permeable sediments with nonmigratory ripples to remove bioavailable nitrogen from coastal ecosystems is lower than that of cohesive sediments. We conclude that while experimental measurements provide a good starting point for constraining key parameters, reactive transport models with realistic kinetic and transport parameters provide critical insight into biogeochemical processes in permeable sediment that are difficult to experimentally evaluate.